Crop Production Summary, Southeast Kansas – 2016 - Gretchen Sassenrath; L. Mengarelli; Jane Lingenfelser; X. Lin; D. E. Shoup (Kansas Agricultural Experiment Station Research Reports, 2017)
Crop production in southeast Kansas is summarized from variety trials and research plot experiments conducted at the Southeast Research and Extension Center fields in 2016.
Keywords: crop production; corn; wheat; soybeans